Measurement and Validity of Jennifer Aaker’s Brand Personality Scale for Close-up Brand - Sekar, P.C.; Thomas, Bejoy John (Indian Journal of Marketing, 2008)
Throughout the past two decades, the development of new products has been a popular marketing strategy for many firms. According to the trade publication New Product News, consumer-product companies launch nearly 20,000 new products each year (compared to only 2,689 in 1980) and supermarkets carry an average of 30,000 products compared to 13,067 in 1982 (as cited in Belch&Belch, 2001)1. Because of an increase in marketplace competition, this newfound brand proliferation threatens the survival of other recent brands. Brand differentiation is now becoming an important tactic for combating competition in this hostile marketplace. A viable solution for establishing the distinctiveness of a brand is through brand personality. Attaching personalities to brands contributes to a differentiating brand identity, which can make brands more desirable to the consumer.